Does financial cooperation agreement improve the cointegration among ASEAN+3 money markets? - Rahman, Md. Saifur; Shahari, Farihana (Taylor & Francis Group, 2017)
This paper aims to empirically examine the degree of cointegration among ASEAN+3 money markets in order to determine and adopt remedial actions pursuant to vulnerabilities in the region’s money markets that indicate an inability to prevent possible financial crises. In order to validate vulnerabilities, this paper investigates the degree to which money markets are integrated. Inter-bank lending rates are divided based on agreement periods as well as on income levels of regional economies. The VAR-based Cointegration test and the VECM have been applied in the investigation process. The findings are: (1) weak integration during the pre-agreement period; (2) substantial progress toward the post-agreement period; (3) both high- and low-income markets integrate in a cooperative way; and (4) the agreement produces an impact that is incomplete in so far as integrating the region’s money markets. The finding of this study offers implications for the regional makers.